Strategi Pengembangan Ekonomi Kreatif dengan Metode Triple Helix untuk Mendukung Program Revitalisasi Save Maninjau - Oknaryana Oknaryana; Tri Kuniawati; Dwi Pratiwi Wulandari; Marwan Marwan (Universitas Negeri Padang, 2023)
Maninjau Lake is a lake with enchanting natural beauty. But unfortunately this lake is polluted by the presence of floating net cages. For this reason, the government launched a Save Maninjau Revitalization Program. Another potential economic sector that can be developed in Lake Maninjau is the tourism sector as well as the creative economy. This article uses a descriptive approach to analyze creative economic development strategies in the tourist village in Maninjau, namely Nagari Sungai Batang. The triple helix approach explores the roles of government, universities and business people in developing their businesses. The results of this study are the profile of creative economy actors in Nagari Sungai Batang. Next, the role of the government, universities and creative economy business actors as a strategy to develop the creative economy sector in Sungai Batang Village